Accounting for Governmental and Nonprofit Entities (Book). - Burns, Thomas J.; Krasniewski, Raymond J. (The Accounting Review, 1981)
Reviews the book "Accounting for Governmental and Nonprofit Entities," by Leon E. Hay.